Minorities in Iran - Elling, R. author. aut Link
VII, 267 p.
Keywords: Based on the premise that nationalism is a dominant factor in Iranian identity politics despite the significant changes brought about by the Islamic Revolution, this cross-disciplinary work investigates the languages of nationalism in contemporary Iran through the prism of the minority issue.